Advances in hepatic arterial perfusion chemotherapy for hepatic metastases - Ou, Haodi; Li, Xiaodong; Chang, Shulin; Li, Guijie; Chen, Feng; Jiang, Song (Frontiers in Oncology, 2025)
Hepatic arterial infusion chemotherapy (HAIC) is one of the local treatment modalities employed for liver metastases. HAIC targets the delivery of chemotherapy drugs to the affected area by inserting a catheter into the tumor’s blood-supplying artery. This approach not only enhances drug concentration within the tumor site, but also significantly reduces systemic side effects. Currently, there are various chemotherapeutic regimens available for HAIC in liver metastases; however, determining the optimal therapeutic agent remains elusive. This article provides a comprehensive review of HAIC dosing regimens and multimodal therapy for liver metastases originating from colorectal, breast, and gastric cancers. Meanwhile, this paper briefly outlines ongoing research on HAIC treatment for liver metastases associated with esophageal cancer, gastroenteropancreatic neuroendocrine tumors, and uveal melanoma.